Mechanisms of glabridin inhibition of integrin αIIbβ3 inside-out signals and NF-κB activation in human platelets - Wei-Chieh Huang; Thanasekaran Jayakumar; Joen-Rong Sheu; Chih-Wei Hsia; Chih-Hsuan Hsia; Ting-Lin Yen; Chao-Chien Chang (Chinese Medicine, 2023)
Abstract Background Platelets play a crucial role in cardiovascular diseases (CVDs) and are activated by endogenous agonists like collagen. These agonists initiate signal transduction through specific platelet receptors, resulting in platelet aggregation. Glabridin, a prenylated isoflavonoid found in licorice root, is known for its significance in metabolic abnormalities. Glabridin has been observed to inhibit collagen-induced platelet aggregation, but the precise mechanisms, specifically concerning NF-κB activation and integrin αIIbβ3 signaling, are not yet fully understood. Methods In this study, platelet suspensions were prepared from healthy human blood donors, and the aggregation ability was observed using a lumi-aggregometer. The inhibitory mechanisms of glabridin in human platelets were evaluated through immunoblotting and confocal microscopy. The anti-thrombotic effects of glabridin were assessed by histological analysis of lung sections in acute pulmonary thromboembolism and by examining fluorescein-induced platelet plug formation in mesenteric microvessels in mice. Results Glabridin inhibited integrin αIIbβ3 inside-out signals such as Lyn, Fyn, Syk, and integrin β3 activation and NF-κB-mediated signal events, with similar potency to classical inhibitors BAY11-7082 and Ro106-9920. Glabridin and BAY11-7082 inhibited IKK, IκBα, and p65 phosphorylation and reversed IκBα degradation, while Ro106-9920 only reduced p65 phosphorylation and reversed IκBα degradation. BAY11-7082 reduced Lyn, Fyn, Syk, integrin β3, phospholipase Cγ2 and protein kinase C activation. Glabridin reduced platelet plug formation in mesenteric microvessels and occluded vessels in thromboembolic lungs of mice. Conclusion Our study revealed a new pathway for activating integrin αIIbβ3 inside-out signals and NF-κB, which contributes to the antiplatelet aggregation effect of glabridin. Glabridin could be a valuable prophylactic or clinical treatment option for CVDs.